Membrane Fatty Acid Composition and Cell Surface Hydrophobicity of Marine Hydrocarbonoclastic Alcanivorax borkumensis SK2 Grown on Diesel, Biodiesel and Rapeseed Oil as Carbon Sources - Konieczna, Maria (Molecules, 2018)
The marine hydrocarbonoclastic bacterium Alcanivorax borkumensis is well known for its ability to successfully degrade various mixtures of n-alkanes occurring in marine oil spills. For effective growth on these compounds, the bacteria possess the unique capability not only to incorporate but also to modify fatty intermediates derived from the alkane degradation pathway. High efficiency of both these processes provides better competitiveness for a single bacteria species among hydrocarbon degraders. To examine the efficiency of A. borkumensis to cope with different sources of fatty acid intermediates, we studied the growth rates and membrane fatty acid patterns of this bacterium cultivated on diesel, biodiesel and rapeseed oil as carbon and energy source. Obtained results revealed significant differences in both parameters depending on growth substrate. Highest growth rates were observed with biodiesel, while growth rates on rapeseed oil and diesel were lower than on the standard reference compound (hexadecane). The most remarkable observation is that cells grown on rapeseed oil, biodiesel, and diesel showed significant amounts of the two polyunsaturated fatty acids linoleic acid and linolenic acid in their membrane. By direct incorporation of these external fatty acids, the bacteria save energy allowing them to degrade those pollutants in a more efficient way. Such fast adaptation may increase resilience of A. borkumensis and allow them to strive and maintain populations in more complex hydrocarbon degrading microbial communities.